South Atlantic meridional overturning circulation and its respective heat and freshwater transports from sustained observations near 34.5°S - Pita, Ivenis; Goes, Marlos; Volkov, Denis L.; Dong, Shenfu; Schmid, Claudia (Frontiers in Marine Science, 2024)
The Atlantic Meridional Overturning Circulation (AMOC) drives northward Meridional Heat Transport (MHT) and affects climate and weather patterns, regional sea levels, and ecosystems. This study uses a methodology recently applied in 22.5°S to estimate the strength and structure of the AMOC, MHT and freshwater (FWT) transports at 34.5°S since 2005. For this, temperature and salinity profiles from sustained observations were used in conjunction with satellite and reanalysis data under two mapping methodologies: (i) an optimized mapping and (ii) a two-layer feed-forward neural network approach. There is strong agreement between both methods for AMOC, MHT and FWT estimates, thus showing the mapping methodologies are robust. In addition, the AMOC variability estimate is significantly correlated with the monthly SAMBA array data (correlation of 0.41). The mean AMOC transport of 17.0 ± 1.6 Sv, a MHT of 0.6 ± 0.1 PW, and a FWT of -0.02 ± 0.01 Sv are estimated between January 2005 and May 2023 at 34.5°S. The MHT and FWT are analyzed in terms of their horizontal (Hhor and Fhor) and overturning contributions (Hov and Fov), and vertical structures. The MHT is dominated by the overturning contribution (correlation of 0.92), while the FWT is controlled by the overturning contribution driven by the wind via Ekman transport at seasonal timescale, and by horizontal contribution at longer timescales. Both horizontal heat (Hhor) and freshwater (Fhor) components are mostly confined to the upper 500 m, with the geostrophic Fov and Fhor offsetting each other between 50 m and 500 m, and the Ekman Fov in the upper 50 m determining the negative FWT. Finally, the estimated mean Fov of -0.15 Sv agrees with previous estimates that the AMOC exports freshwater in the South Atlantic, and suggests that the AMOC is unstable. Although a long-term trend in the Fov was not detected in the past 20 years, there is a salinification trend (0.05 ± 0.01 PSU/decade) in the upper 300 m near 34.5°S since 2005.